Tinjauan Pemasaran Pariwisata Melalui Teknologi Informasi Sebagai Perencanaan Manajemen Industri Pariwisata : Suatu Kajian Literatur - Edi Irawan (Dharma Ekonomi, 2023)
This article aims to review and seek to inform about the concept of reviewing tourism marketing through information technology as a tourism industry management plan. The research method used is qualitative and literature studies or library research Based on the results and discussion, it can be concluded theoretically that to understand tourism marketing reviews through information technology as a management model planning in the tourism industry requires several important things including: (a) Travel consumer, (b) Trends in tourism technology, (c ) Digital Marketing (DM) and (d) Virtual Reality (VR). Technology is a central element and a foundation for actors in the tourism industry promoting media that is relevant to the development of information technology, especially in the form of social media and websites.